Academic Stress in Students A Review - Mishra, Puja; Choudhuri, Rashmi (JOURNAL OF INDIAN EDUCATION, 2020)
Everyone is focusing on performance, competition and perfection, which leads to menacing increase in stress. The signs of stress and its consequences are omnipresent. Every individual spends sufficient duration of their life in studying, therefore it is likely to have some kind of academic stress. This article examines what existing literature reveals about academic stress, particularly, attention paid to the sources of academic stress and its impact on students. Firstly, concept of stress is described and existing literature on students’ stress is reviewed in light of two questions, which are the different sources of stress and how stress is affecting students. This article includes review of researches done in India and abroad with particular attention being directed to academic setting.